2010
DOI: 10.1057/jt.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Tracing customer orientation and marketing capabilities through retailers’ websites: A strategic approach to internet marketing

Abstract: The study extends the concepts of customer orientation and marketing capabilities to an online retailing context while it examines the ability of product involvement to distinguish retailers ' websites. The objectives of this article are: (a) to identify the degree of customer orientation as manifested on retailers ' websites, (b) to investigate the marketing capabilities revealed through their websites and (c) to examine the role of involvement as a differentiating factor in an online context. A twofold metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In fact, it is cheaper to open a profile on a social network than to design a web page with a large number of functions that would have to be updated constantly. Fourth, the websites of the pharmacies studied were oriented toward a more informative strategy than a relational one, an aspect that has been found in other sectors (Escobar-Rodríguez and Carvajal-Trujillo, 2013; Tsiotsou, Rigopoulou and Kehagias, 2010) and fits the traditional “one-way” marketing strategy followed by the pharmaceutical sector (Rader et al , 2014). However, in absolute terms, the informative items presented on the websites were not very numerous.…”
Section: Discussionmentioning
confidence: 84%
“…In fact, it is cheaper to open a profile on a social network than to design a web page with a large number of functions that would have to be updated constantly. Fourth, the websites of the pharmacies studied were oriented toward a more informative strategy than a relational one, an aspect that has been found in other sectors (Escobar-Rodríguez and Carvajal-Trujillo, 2013; Tsiotsou, Rigopoulou and Kehagias, 2010) and fits the traditional “one-way” marketing strategy followed by the pharmaceutical sector (Rader et al , 2014). However, in absolute terms, the informative items presented on the websites were not very numerous.…”
Section: Discussionmentioning
confidence: 84%
“…Further, Mallya (2003) argues that public sector banks need to redefine the customer service parameters so as to compete with the private sector banks, which are widely perceived as being more customer-oriented. Moreover, market-oriented companies are expected to extract relevant information so as to arrive at better decisions that are useful in achieving specific and determined performance indicators (Tsiotsou, 2010;Matson & Mentzer, 2000). Sathye (2005) also opines that private banks have continued to show improved performance and efficiency as compared to public sector banks.…”
Section: Methodsmentioning
confidence: 99%
“…Assistive intent of the web site reflects the e-seller's customer orientation, which refers to the degree of care and support provided by the web site to satisfy customers' needs and facilitate their purchase decisions (Saxe and Weitz, 1982;Poddar et al, 2009). While the outcomes of such orientation have been widely studied in traditional retailing, investigation of these concepts in the online shopping context has been very limited (Poddar et al, 2009;Tsiotsou et al, 2010). Indeed, a recent study by Tsiotsou et al (2010) showed that customer orientation is not highly visible on the web sites of E-retailers.…”
Section: Introductionmentioning
confidence: 99%
“…While the outcomes of such orientation have been widely studied in traditional retailing, investigation of these concepts in the online shopping context has been very limited (Poddar et al, 2009;Tsiotsou et al, 2010). Indeed, a recent study by Tsiotsou et al (2010) showed that customer orientation is not highly visible on the web sites of E-retailers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation